A novel, liver-specific long noncoding RNA LINC01093 suppresses HCC progression by interaction with IGF2BP1 to facilitate decay of GLI1 mRNA. (28th May 2019) - He, Jia; Zuo, Qiaozhu; Hu, Bo; Jin, Haojie; Wang, Cun; Cheng, Zhuoan; Deng, Xuan; Yang, Chen; Ruan, Haoyu; Yu, Chengtao; Zhao, Fangyu; Yao, Ming; et al.
Abstract: Long noncoding RNAs (lncRNAs) are implicated as novel drivers in hepatocellular carcinoma (HCC), but the underlying mechanisms of this relationship with hepatocarcinogenesis are unknown. We report a novel, liver-specific lncRNA LINC01093 that shows significant downregulation in HCC tissues. LINC01093 expression is inversely correlated with cancer embolus and HCC TNM stage and as a prognostic predictor for HCC patients. LINC01093 overexpression significantly suppresses HCC cell proliferation and metastasis in vitro and in vivo . Conversely, its knockdown promotes HCC progression. Mechanistic analyses indicate that LINC01093 directly binds insulin-like growth factor 2 mRNA–binding protein 1 (IGF2BP1), interfering with interaction between IGF2BP1 and glioma-associated oncogene homolog 1 (GLI1) mRNA. The result is degradation of GLI1 mRNA, further affecting expression of GLI1 downstream molecules involved in HCC progression. The liver-enriched lncRNA LINC01093 is a promising prognostic indicator for HCC patients, and the newly identified LINC01093–IGF2BP1–GLI1 axis shows potential for therapeutic targets in HCC. Highlights: Liver-specific LINC01093 is downregulated in HCC tissues and prognostic in HCC. LINC01093 inhibits HCC cell proliferation and metastasis in vitro and in vivo. LINC01093 facilitates mRNA decay of GLI1 via interacting with IGF2BP1 in HCC cells. GLI1 is required for LINC01093 regulation of HCC cell progression. The LINC01093–IGF2BP1–GLI1 axis offers potential biomarkers for HCC.